2008
DOI: 10.1186/1471-2172-9-6
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of celiac disease autoantibodies after in vitro gliadin challenge is dependent on small-bowel mucosal transglutaminase 2-specific IgA deposits

Abstract: Background: In celiac disease gluten, the disease-inducing toxic component in wheat, induces the secretion of autoantibodies which are targeted against transglutaminase 2 (TG2). These autoantibodies are produced in the smallintestinal mucosa, where they can be found deposited extracellularly below the epithelial basement membrane and around mucosal blood vessels. In addition, during gluten consumption these autoantibodies can also be detected in patients' serum but disappear from the circulation on a gluten-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 25 publications
(46 reference statements)
3
23
0
Order By: Relevance
“…More recently, similar data have been obtained measuring IgA anti-TG2 antibodies in supernatants of cultured biopsies from CD patients untreated and on a gluten-free diet [15][16][17]. This test has been proposed for diagnostic purposes, particularly in patients with normal mucosa.…”
Section: Introductionsupporting
confidence: 51%
See 2 more Smart Citations
“…More recently, similar data have been obtained measuring IgA anti-TG2 antibodies in supernatants of cultured biopsies from CD patients untreated and on a gluten-free diet [15][16][17]. This test has been proposed for diagnostic purposes, particularly in patients with normal mucosa.…”
Section: Introductionsupporting
confidence: 51%
“…Detection of anti-endomysium antibodies (EMA) and anti-TG2 IgA antibodies in faecal supernatants from CD patients was determined to be unreliable as a diagnostic test [25]. The search for anti-TG2 antibodies in culture supernatants of intestinal biopsy from CD patients by ELISA was proposed in particular to improve the accuracy of CD diagnosis in subjects with mild enteropathy and in patients negative for serum antibodies [15][16][17]. More recently, using immunofluorescence, Korponay-Szabo et al [7] showed that IgA deposited in the intestine of CD patients are directed against TG2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We know nowadays that gluten or gliadin, when incubated with primary cultures of CD patients on glutenfree diet,induces morphological as well as immunological aberrations. Cytokine release, autoantibodies secretions, increased CD25+ cell density, MHC class 1chain-related gene A expression were reported [43,44]. Applying genetic bioinformatics, it was shown that important dysfunction of pathogenic networks related to cell to cell communications, intracellular signaling, ubiquitin-proteasome system, cell cycle and apoptosis and extracellular matrix modulation resulted from acute gliadin effects on mucosal biopsies of CD patients, while on gluten withdrawal [45].…”
Section: Discussionmentioning
confidence: 99%
“…In IgA-deficient patients, these mucosal autoantibodies appear in the IgM-class instead. Their secretion in vitro on gliadin challenge is dependent on their mucosal deposits [16]. The measurement of ABs secreted into intestinal biopsies cultured supernatants has higher sensitivity and specificity than the detection of mucosal deposits and they can predict evolution towards mucosal atrophy [17].…”
Section: Anti Tg2 Abs Secretion Binding and Distributionmentioning
confidence: 99%